RESPON MUTU PISANG KULTIVAR MAS KIRANA TERHADAP KEMASAN ATMOSFER TERMODIFIKASI AKTIF - Pradhana, Adhitya Yudha (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Major constraints and problems associated with postharvest handling of fresh banana are short shelf life and lack of proper postharvest handling. The purpose of this study was to evaluate fruit quality and shelf life under MAP packaging, with or without KMnO4. This research was conducted between May-August 2013 at the laboratory of food processing and agricultural product, Bogor Agricultural Institute. The data obtained were analyzed with analysis of variance (ANOVA), if the results were significant at 5%, then further test was carried out with Duncan test. The results indicated that the shelf life of bananas packaged in White Stretch Film (WSF) with KMnO4 (MAP active) at 28Â°C could be stored for 10 days and comparable to 6 days without KMnO4 (MAP passive), and the shelf life of fruit packed in MAP active at 15Â°C could be stored for 24 days and comparable to 16 days for MAP passive. The 3 factors interaction were significant at different levels of starch content at 6th day, whereas total soluble solids (TSS) was significantly different at 2nd day of storage. MAP active treatment could delay starch content degradation and TSS when compared to passive MAP.